Colorectal cancer lymph node staining by activated carbon nanoparticles suspension in vivo or methylene blue in vitro - Cai, Hong-Ke (World journal of gastroenterology : WJG, 2012)
AIM：To investigate whether activated carbon nanoparticles suspension（ACNS） or methylene blue（MB） can increase the detected number of lymph nodes in colorectal cancer.METHODS：Sixty-seven of 72 colorectal cancer patients treated at our hospital fulfilled the inclusion criteria of the study which was conducted from December 2010 to February 2012.Seven patients refused to participate.Eventually,60 patients were included,and randomly assigned to three groups（20 in each group）：ACNS group（group A）,MB group（group B） and non-stained conventional surgical group（group C）.In group A,patients received subserosal injection of 1 mL ACNS in a 4-quadrant region around the mass.In group B,the main artery of specimen was identified and isolated after the specimen was removed,and 2 mL MB was slowly injected into the isolated,stretched and fixed vessel.In group C,no ACNS and MB were injected.All the mesentery lymph nodes were isolated and removed systematically by visually inspecting and palpating the adipose tissue.RESULTS：No difference was observed among the three groups in age,gender,tumor location,tumor diameter,T-stage,degree of differentiation,postoperative complications and peritoneal drainage retention time.The total number of detected lymph nodes was 535,476 and 223 in the three groups,respectively.The mean number of detected lymph nodes per patient was significantly higher in group A than in group C（26.8 ± 8.4 vs 12.2 ± 3.2,P 0.001）.Similarly,there were significantly more lymph nodes detected in group B than in group C（23.8 ± 6.9 vs 12.2 ± 3.2,P 0.001）.However,there was no significant difference between group A and group B.There were 50,46 and 32 metastatic lymph nodes dissected in 13 patients of group A,10 patients of group B and 11 patients of group C,without significant differences among the three groups.Eleven of the 60 patients had insufficient number of detected lymph nodes（ 12）.Only one patient with T 4a rectal cancer had 10 lymph nodes detected in group B,the other 10 patients were all from group C.Based on the different diameter categories,the number of detected lymph nodes in groups A and B was significantly higher than in group C.However,there was no statistically significant difference between group A and group B.The metastatic lymph nodes were not significant different among the three groups.Similarly,tumor location,T stage and tumor differentiation did not affect the staining results.Body mass index was a minor influencing factor in the two different staining methods.The stained lymph nodes can easily be identified from the mesenteric adipose tissues,and the staining time for lymph nodes was not significantly different compared with unstained group.None of the patients in groups A and B had drug-related complications.CONCLUSION：Both activated carbon nanoparticles suspension in vivo and methylene blue in vitro can be used as tracers to increase the detected number of lymph nodes in colorectal cancer.